THE EFFECT OF GYM BALL USE DURING PREGNANCY ON THE LABOR PROCESS AT THE INDEPENDENT MIDWIFE PRACTICE OF SUPIANI, S.KEB, MEDAN DELI SUB-DISTRICT - Siti Arfah Siregar; Rismaida Saragih (Journal of Innovative and Creativity, 2026)
The purpose of this study was to examine the effect of gym ball use during pregnancy on the duration and progress of labor at the Independent Midwife Practice of Supiani, S.Keb, in 2025. Prolonged labor remains a significant contributor to maternal and neonatal morbidity and mortality, particularly in low-resource settings. Non-pharmacological interventions, such as the use of a birthing or gym ball, are increasingly recommended as supportive strategies to facilitate labor through improved maternal positioning, comfort, and pelvic engagement. Materials and Methods. This quantitative study employed a quasi-experimental design with a pre-post control group format. The total sample consisted of 30 third-trimester pregnant women, divided into a treatment group (n=24) and a control group (n=6). The treatment group participated in prenatal gym ball sessions once per week for four weeks. Data were collected through secondary records, observation checklists, and the Hamilton Anxiety Rating Scale (HARS). Univariate and bivariate analyses were conducted, and a Chi-square test was applied to assess the relationship between gym ball use and labor duration. Results. The majority of respondents who used the gym ball (100%) experienced a faster labor process, while 50% of those who did not participate experienced prolonged labor. Statistical analysis revealed a significant association between gym ball use and the acceleration of labor (p-value = 0.005). Conclusions. Gym ball use during pregnancy significantly contributes to shorter labor duration and supports a more efficient labor process. Integrating gym ball exercises into antenatal care may enhance maternal outcomes and reduce the need for medical interventions.